Across the universe : the past, present, and future of the crossword puzzle - Last, Natan (Pantheon Books, 2025)
"An entertaining and eye-opening look at the history of the crossword, who constructs it, and why it matters as both a reflection of and influence on our culture. From WORDLE to SPELLING BEE, we live in a time of word game mania. Crosswords, in particular, gained renewed popularity during the Covid-19 lockdown, when games became another kind of refuge. Today, 36 million Americans solve crosswords once a week or more, and nearly 23 million solve them daily. Yet, as longtime New Yorker crossword contributor Natan Last will tell you, the seemingly apolitical puzzle has never been more controversial. In recent years, popular puzzle makers like The New York Times-the original and still the gold standard for word games-have been challenged for the way they prioritize certain cultures and perspectives as either the norm (read: white and male) or obscure (everyone else). At the same time, the crossword has never been more democratic. A larger, younger, more tech-savvy, and solidaristic group of people have fallen in love with puzzle solving, ushering in a more inclusive rise to the kinds of people constructing them, challenging the very idea of them and, in fact, what "normal" actually is. With a critical eye toward its history, Natan Last explores the debates about the future of the crossword and investigates those who want the puzzle to transform into a tool of progressivism; ultimately, asking if the crossword can help us reshape the world. Across the Universe interrogates all the ways words-and the games we make using those words-change our culture while bringing us into the worlds of those pushing for the crosswords' much-needed evolution"--